1989
DOI: 10.1007/bf02279865
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic maculopathy in a Jamaican population

Abstract: Maculopathy is the commonest cause of severe visual loss from diabetic retinopathy in Jamaica [5]. Ophthalmic assessment of 158 black Jamaican maturity onset diabetics referred randomly from the primary and secondary health centres, demonstrated maculopathy in 48% of patients. Duration of diabetes was a strong risk factor for maculopathy (p less than 0.001). Poor compliance with diabetic and hypertensive therapy may influence the prevalence of maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Duration of diabetes is known to be an independent, and perhaps one of the most important, risk factors for retinopathy [31,32]. In the present study, a significant association was observed with DR and duration of diabetes, similar to that reported in several other studies [33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…Duration of diabetes is known to be an independent, and perhaps one of the most important, risk factors for retinopathy [31,32]. In the present study, a significant association was observed with DR and duration of diabetes, similar to that reported in several other studies [33][34][35].…”
Section: Discussionsupporting
confidence: 92%